Prolonged exposure of resveratrol induces reactive superoxide species–independent apoptosis in murine prostate cells. Issue 10 (October 2017) - Kumar, Sanjay; Stokes, James; Singh, Udai P; Scissum-Gunn, Karyn; Singh, Rajesh; Manne, Upender; Mishra, Manoj K
Nitric oxide, a signaling molecule, inhibits mitochondrial respiration by binding with cytochrome c oxidase, resulting in elevated production of reactive superoxide species (reactive oxygen and nitrogen) in the mitochondria and increased susceptibility to cell death. Generation of mitochondrial superoxide species can be suppressed by natural compounds such as resveratrol, a dietary polyphenol found in the skin of red fruits. In various cancer cells, resveratrol shows anti-oxidant and cancer preventive properties. Since, the effect of resveratrol on reactive superoxide species–independent apoptosis in prostate cancer cells is not well illustrated; therefore, we investigated this phenomenon in TRAMP murine prostate cancer cells. To accomplish this, TRAMP cells were incubated with resveratrol, resveratrol + DETA-NONOate, DETA-NONOate (nitric oxide donor), resveratrol + L-NMMA, or L-NMMA (nitric oxide inhibitor) for 48 h, and reactive superoxide species in the mitochondria and culture supernatant were measured. In addition, the mitochondrial membrane potential, cell viability, expression of apoptotic markers (Bax and Bcl2), γ-H2A.x, p53, and caspase-3 was determined. We found that resveratrol suppressed reactive superoxide species such as reactive oxygen species in the mitochondria and nitric oxide in culture supernatant when compared to the DETA-NONOate treatment and disrupted the mitochondrial membrane potential. Resveratrol also reduced cell viability, altered the expression of apoptotic markers (Bax and Bcl2), and increased expression of γ-H2A.x (indicative marker of DNA fragmentation) and p53 (a critical DNA damage response protein). However, there was no appreciable modulation of the caspase-3. Therefore, our data suggest that resveratrol induces superoxide species–independent apoptosis and may act as a therapeutic agent against prostate cancer.